Immobilization stress increased cytochrome P450 1A2 (CYP1A2) expression in the ovary of rat - Jong-Chan Hwang; Hwan-Deuk Kim; Byung-Joon Park; Ryoung-Hoon Jeon; Su-Min Baek; Seoung-Woo Lee; Min Jang; Seul-Gi Bae; Sung-Ho Yun; Jin-Kyu Park; Young-Sam Kwon; Seung-Joon Kim; et al. (The Korean Society of Animal Reproduction and Biotechnology, 2021)
Under the stressed condition, a complex feedback mechanism for stress is activated to maintain homeostasis of the body and secretes several stress hormones. But these stress hormones impair synthesis and secretion of the reproductive hormones, followed by suppression of ovarian function. Cytochrome P450 1A2 (CYP1A2) plays a major role in metabolizing exogenous substances and endogenous hormones, and its expression is recently identified at not only the liver but also several organs with respect to the pancreas, lung and ovary. Although the expression of CYP1A2 can be also affected by several factors, understanding for the changed pattern of the ovarian CYP1A2 expression upon stress induction is still limited. Therefore, CYP1A2 expression in the ovaries from immobilization stress-induced rats were assessed in the present study. The stress-induced rats in the present study exhibited the physiological changes in terms of increased stress hormone level and decreased body weight gains. Under immunohistological observation, the ovarian CYP1A2 expression in both control and the stressed ovary was localized in the antral to pre-ovulatory follicles. However, its expression level was significantly (p < 0.01) higher in the stress-induced group than control group. In addition, stress-induced group presented more abundant CYP1A2-positive follicles (%) than control group. Since expression of the ovarian CYP1A2 was highly related with follicle atresia, increased expression of CYP1A2 in the stressed ovary might be associated with changes of the ovarian follicular dynamics due to stress induction. We hope that these findings have important implications in the fields of the reproductive biology.